The prohibition of paratransit services in Harare Zimbabwe and its implications - Kutshwa, Nokuthula (Department of Civil Engineering, 2026)
Background A ban on ‘mushika shika' was officially announced in March 2020 by the Government of Zimbabwe (GoZ) citing the need to curb the spread of COVID-19. Since 2016, the GoZ has been trying to restrict the ‘mushika shika' from entering the CBD of Harare. ‘Mushika shika' – stemming from the Zulu word for hustle – refers to unregulated illegal vehicles that operate an alternative form of public transport. Aim This study investigates whether the ban of ‘mushika shika' in Harare, Zimbabwe was an appropriate policy decision. The impacts brought about by the ban or prohibition are investigated. The researcher uses the impacts to assess whether prohibition was necessary. Method Research methods consisted of both a quantitative and qualitative study. The indicative quantitative study was aligned to a (2021, n=23) non-probability survey conducted with commuters, while the qualitative study was used for (2021, n=7) interviews conducted with ZUPCO, commuter omnibus operators, and ‘mushika shika' operators. City of Harare (CoH) officials did not participate in the interview and secondary sources were used to gather data aligned to the local authority. Representatives of local government authorities fear divulging information and would rather not be involved in surveys or research. Qualitative data analysis involved thematic analysis to derive patterns. Interpretive phenomenological analysis was also applied to interpret operators' experiences of the ‘mushika shika' ban. Quantitative data analysis was done through descriptive statistics. The data collection tools used were structured interview questions and an online questionnaire survey. Site observation was also used to supplement the interviews and survey data. Findings The results of the study show that the ban of ‘mushika shika' led to a situation where the demand was greater than the supply. The formal public transport service ZUPCO was inundated and unable to meet demand. The impacts on people that rely on public transport were severe. Most respondents indicated that they prefer using ‘mushika shika' as they have attributes nonetheless such as flexibility, which is absent on the regulated transport sectors. ‘Mushika shika' has a downside of poor safety and security, which the captive public transport user in Harare is forced to ignore as there are no other public transport options. Discussion The research findings show that the public transport challenges being experienced in Harare after the ban of ‘mushika shika' are serious and have had negative impacts to the commuters and all the informal and formal operators. The macro-economic climate and poor governance have contributed to an ailing public transport system in Harare and Zimbabwe as a whole. The opportunity to interview the formal and informal public transport sector has shed light on the different challenges the operators are experiencing, due to their different operation environments in terms of regulations. Commuters who were viewed as the end users, have suffered considerably. For instance, women were observed by the media, climbing onto the back of open vehicles and travelling to destinations while standing in dangerous positions. Commuters have been forced to wait for transport in long queues for more than two hours in crowded places that are not safe or succumb to walking long distances. Conclusions The researcher concluded that, despite the illegal status of ‘mushika shika,' the ban was not sufficiently evaluated beforehand and therefore inappropriate. The root causes for influx of the illegal paratransit must be investigated and resolved by public transport specialist. The economic crisis, collapse of transport infrastructure, absence of regulation and policies, lack of expertise are some of the root causes of poor service delivery by the regulated transport operators. This has created a gap that the paratransit sector has taken advantage of.